Landau parameter of elasticity - Merabtine, N.; Bousnane, Z.; Benslama, M.; Boussaad, F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Based on the consideration given by the Ginzburg-Landau (GL) theory according to the variational principle, we assume that the microscopic Gibbs function density given by [1] ∫VGsdV = ∫(Fs - 1/4pBH)dv must be stationary at the thermodynamical equilibrium. To describe the universal propagation of the order parameter, we express order phases and amplitudes as dealing with tensor elements. In addition to the variation of the order parameter and the vector potential limited by the condition )()( xBxArrr =×∇ , we introduce here the concept of elasticity to describe the propagation of the superconducting state as “the little waves borning on smooth Superconductor Sea [2]”. The coherence concept transits to the asymptotic behaviour, we shall say that equivalence concept is its limit, this must transgress the propagation laws of superconductivity to be replaced by the increasing of superconductivity. Superconductivity will be viewed as second order extensive value, propagation seems to be so quick to avoid the stability, the increasing of superconductivity requires more time, and more time will be equivalent to a second and added measurement process eliminating the degeneracy of the first integral during the cooling process. It may deal with the first approximated stability of Superconductor State. The uncertainly in quantum mechanics is limited as scale length relations for the dimension coherence of the order parameter and temperatures.